The diagnostic significance of cardiac biomarkers in veterinary medicine - POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
Cardiac biomarkers are a group of proteins that have been extensively studied in human and veterinary medicine during the past decades, regarding their diagnostic and prognostic importance in heart disease. Moreover, cardiac biomarkers have been evaluated for their efficacy in the assessment of clinical staging of heart disease, risk stratification of patients, selection of therapeutic regimens and prognosis of cases. Cardiac biomarkers are broadly classified, according to their role in the pathophysiology of heart failure, into markers of myocardial injury (cardiac troponins, creatine kinase MB isoenzyme), myocyte stress (natriuretic peptides), inflammation (acute phase proteins), cardiac remodelling (matrix metalloproteinases), neurohormonal and endothelial dysfunction (endothelin, aldosterone, rennin, norepinephrine). It is unlikely that all of the aforementioned biomarkers will eventually be applied in clinical practice. Nevertheless, some of them (cardiac troponins, natriuretic peptides) have already been available commercially and established as part of the diagnostic investigation in heart disease. This review article focuses on the role of both established and potential cardiac biomarkers in veterinary medicine.